Comparing the equator principles' IFC performance standard 6 and the South African mining and biodiversity guideline to identify areas of overlap and gaps to improve biodiversity conservation in the mining sector - Ncube, Nhlanhla Brian (My University, 2015)
Environmental degradation and pollution continue to characterise the mining sector in South Africa despite a robust legislative framework which is aimed at enhancing sustainable mining practices. Of particular concern is the impact of mining on biodiversity. During 2013 the Departments of Environmental Affairs and Mineral Resources, together with the South African Mining and Biodiversity Forum, an alliance of stakeholders from industry, conservation organisations and government facilitated by the Chamber of Mines of South Africa, released the South African Mining and Biodiversity Guideline (SAMBG), which aim to mainstream biodiversity into the mining sector. The guideline seek to integrate biodiversity considerations into planning processes and manage biodiversity through the lifecycle of a mine, and so contribute to better outcomes. In addition to the guideline, mining companies that obtain funding from financial institutions that are signatory to the Equator Principles are required to implement IFC Performance Standard 6 (IFC PS6) which also deals with biodiversity conservation. There is a concern that the SAMBG adds further to the burgeoning pile of standards, guidelines and best practices that mining companies are required to meet, but without necessarily adding anything new. This research project deals with this concern through a review of the SAMBG to assess their potential contribution to biodiversity conservation and to determine, through a comparative analysis, whether any overlaps and gaps exist between the guideline and IFC PS6. A qualitative methodology was used to understand how the Aichi Biodiversity Targets are addressed by the SAMBG. Based on this review a conclusion as to the role of the SAMBG amongst the range of guidelines and standards was drawn. The research indicated that there is alignment between the SAMBG, the IFC PS6, the Aichi Biodiversity Targets and South African national environmental legislation. They all aim to achieve a similar outcome, the conservation and sustainable use of biodiversity, but provided different levels of detail and are targeted at slightly different audiences.
A research report submitted to the Faculty of Science, in partial fulfilment of the requirements for the degree of Master of Science, University of the Witwatersrand, Johannesburg, 6 November 2015.
Keywords: Biodiversity conservation.; Mining corporations--South Africa.; Mines and mineral resources.